Acute effects of winter air pollution on respiratory function in schoolchildren in southern England. Issue 2 (1st February 2003) - Peacock, J L; Symonds, P; Jackson, P; Bremner, S A; Scarlett, J F; Strachan, D P; Anderson, H R
Abstract : Aim: To investigate the acute health effects of winter outdoor air pollution (nitrogen dioxide (NO2 ), ozone (O3 ), sulphur dioxide (SO2 ), sulphate (SO4 2− ), and particles (PM10 )) on schoolchildren in an area of southern England where levels of SO2 had been reported to be high. Methods: A total of 179 children, aged 7–13, from three schools (two urban and one rural location), were included. Peak expiratory flow rate (PEFR) and presence or absence of upper respiratory infections were recorded on 63 school days from 1 November 1996 to 14 February 1997. Air pollution and meteorological data were taken from monitors at each school site. The analysis regressed daily PEFR on pollutant level adjusting for confounders and serial correlation and calculated a weighted pooled estimate of effect overall for each pollutant. In addition, large decrements in PEFR were analysed as a binary outcome. Same day, lag 1, lag 2, and a five day average of pollutant levels were used. Results: There were no clear effects of any pollutant on mean PEFR. In addition, we analysed large PEFR decrements (a binary outcome), observing consistent negative associations with NO2, SO4 2−, and PM10, although few lag/pollutant combinations were significant: odds ratios (95% CI) for five day average effect: NO2 24 h average 1.043 (1.000 to 1.089), SO4 2− 1.090 (0.898 to 1.322), PM10 1.037 (0.992 to 1.084). The observed effects of PM10 (only) were stronger in wheezy children (1.114 (1.057 to 1.174)). There were no consistent negative associations between large decrements and ozone or SO2 . Conclusions: There is no strong evidence for acute effects of winter outdoor air pollution on mean PEFR overall in this area, but there is evidence for negative effects on large PEFR decrements.